2013
DOI: 10.1371/journal.pone.0052722
|View full text |Cite
|
Sign up to set email alerts
|

Epidemics of Community-Associated Methicillin-Resistant Staphylococcus aureus in the United States: A Meta-Analysis

Abstract: Staphylococcus aureus is the most frequent cause of skin and soft tissue infections in humans. Methicillin-resistant strains of S. aureus (MRSA) that emerged in the 1960s presented a relatively limited public health threat until the 1990s, when novel community-associated (CA-) MRSA strains began circulating. CA-MRSA infections are now common, resulting in serious and sometimes fatal infections in otherwise healthy people. Although some have suggested that there is an epidemic of CA-MRSA in the U.S., the origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 40 publications
4
84
0
2
Order By: Relevance
“…15,30,36 Additionally, a recent meta-analysis suggested that the communityassociated MRSA epidemic may have peaked earlier in children than in adults. 37 Evaluation of respiratory, sterile site, and other non-SSTIs cultures suggest that MSSA predominates in these infections as compared with SSTIs. Although sterile site isolates represented a minority of infections in this study, these isolates were consistently more likely than SSTI isolates to be oxacillin-susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…15,30,36 Additionally, a recent meta-analysis suggested that the communityassociated MRSA epidemic may have peaked earlier in children than in adults. 37 Evaluation of respiratory, sterile site, and other non-SSTIs cultures suggest that MSSA predominates in these infections as compared with SSTIs. Although sterile site isolates represented a minority of infections in this study, these isolates were consistently more likely than SSTI isolates to be oxacillin-susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…Nosocomial infections overwhelmingly dominate cases where MDR pathogens are implicated, but drug-resistant infections are increasingly becoming common in the community. This has been especially true with the emergence of communityacquired MRSA [3].…”
mentioning
confidence: 99%
“…1 The incidence of SSTIs is increasing, 2 in part due to emergence of methicillin resistant Staphylococcus aureus. 3 Infectious Diseases Society of America guidelines for the management of SSTIs suggest that antibiotic courses of 5 days are effective in cases of nonpurulent cellulitis, with extension of treatment as indicated in cases without notable clinical improvement in that time. 4 Short courses of antibiotics may be beneficial to help prevent development of resistant bacteria, lessen cost, and reduce the abstract BACKGROUND AND OBJECTIVE: Short courses of antibiotics are often indicated for uncomplicated skin and soft tissue infections (uSSTIs).…”
mentioning
confidence: 99%